Tissue culture laboratory induction for undergraduates 2023 / Nur Fathiah Mohd Radzi and Dr. Gurmeet Kaur Surindar Singh - Mohd Radzi, Nur Fathiah; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
A half-day workshop dedicated to the students enrolled in the Research Project course (PHC 632) was held on March 31, 2023, at the Tissue Culture (TC) Unit, Level 6, FF3 Building, Faculty of Pharmacy, UiTM Puncak Alam. The workshop, which was the TC Unit’s first induction, involved nine undergraduate participants currently engaged in final-year projects within the Faculty of Pharmacy and Faculty of Allied Health Sciences, UiTM. The goal of the workshop was to familiarise participants with the fundamentals of cell culture as well as brief them on the policies and procedures of the tissue culture laboratory before they began the experiments. The workshop consisted of three sessions. The first session began with a briefing on safety and health in the laboratory by the head of the TC Unit, Dr. Mashani Mohamad. In this session, attendees were also introduced to the internet laboratory integrated site system (iLISS) for laboratory and equipment booking purposes.